(untitled) (Res Medica, 2013)
For centuries, the functions of sleep have been researched. Multiple theories have been developed, but even now, scientists are unable to produce a conclusive explanation as to why we sleep. It is evident that sleep is vital, as even in animals, it has been argued that sleep deprivation leads to serious consequences. More recently, research has suggested that sleep plays a role in memory consolidation. This review aims to bring together the evidence concerning the link between sleep and different memory sub-classifications (episodic memory, semantic memory, procedural memory and conditioning) and its potential clinical application will be discussed.